2016
DOI: 10.1128/aac.03022-15
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin Tolerance in the Staphylococcus aureus pitA6 Mutant Is Due to Upregulation of the dlt Operon

Abstract: dUnderstanding the mechanisms of how bacteria become tolerant toward antibiotics during clinical therapy is a very important object. In a previous study, we showed that increased daptomycin (DAP) tolerance of Staphylococcus aureus was due to a point mutation in pitA (inorganic phosphate transporter) that led to intracellular accumulation of both inorganic phosphate (P i ) and polyphosphate (polyP). DAP tolerance in the pitA6 mutant differs from classical resistance mechanisms since there is no increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 49 publications
4
25
0
Order By: Relevance
“…5B,C,D,E,F,G) indicated that AFN-1252 and daptomycin still had bacteriostatic activity. It is therefore likely that this increase in survival after 3 exposures was due to the acquisition of tolerance to daptomycin, which is consistent with a previous study [29].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…5B,C,D,E,F,G) indicated that AFN-1252 and daptomycin still had bacteriostatic activity. It is therefore likely that this increase in survival after 3 exposures was due to the acquisition of tolerance to daptomycin, which is consistent with a previous study [29].…”
Section: Resultssupporting
confidence: 91%
“…Although the combination of daptomycin and AFN-1252 prevented the acquisition of resistance to either antibiotic, we did observe the emergence of tolerance to the lipopeptide antibiotic after the third exposure to the drugs. The acquisition of daptomycin tolerance has been reported previously and was found to occur via increased expression of the dltABCD operon, although the mechanism by which this reduced susceptibility was unclear [29]. Crucially, however, whilst this tolerance phenotype reduces the ability of the daptomycin/AFN-1252 combination to kill S. aureus , the antibiotics are still able to inhibit bacterial growth.…”
Section: Discussionmentioning
confidence: 81%
“…Modification of both WTA and LTA parent polymers can have vast impact on function. For instance, D-alanine (D-Ala) ester addition by the dltABCD operon has been shown to regulate autolysis during cell wall remodeling (16), localize penicillin-binding proteins (17), and confer resistance to antibiotics such as daptomycin (18) and antimicrobial peptides (19)(20)(21). The D-alanylation pathway is currently the most well defined (20,22,23), whereby DltA loads the carrier protein DltC with D-Ala.…”
Section: Importancementioning
confidence: 99%
“…The same antibiotics that kill susceptible cells by targeting active metabolic processes (15) are unlikely to kill tolerant variants with a reduced metabolism (16). Therefore, it is not surprising that even strains with antibiotic MICs below susceptibility breakpoints can be drug tolerant, as previously shown by our group (13) and others (12).…”
mentioning
confidence: 78%
“…However, a heteroresistant strain contains cell subpopulations with different levels of antibiotic resistance (10). The mechanism of tolerance is completely different from that of resistance (11)(12)(13)(14). For example, quinolone persistence in S. aureus is attributed to a decrease in ATP levels (8).…”
mentioning
confidence: 99%